AN APPROACH FOR THE OPTIMUM HYDRODYNAMIC DESIGN OF HYDROKINETIC TURBINE BLADES - Shinomiya, L. D.; Vaz, J. R. P.; Mesquita, A. L. A.; de Oliveira, T. F.; Brasil Jr, A. C. P.; Silva, P. A. S. F. (Revista de Engenharia Térmica, 2015)
This work aims to develop a simple and efficient mathematical model applied to optimization of horizontal-axis hydrokinetic turbine blades considering the cavitation effect. The approach uses the pressure minimum coefficient as a criterion for the cavitation limit on the flow around the hydrokinetic blades. The methodology corrects the chord and twist angle at each blade section by a modification on the local thrust coefficient in order to takes into account the cavitation on the rotor shape. The optimization is based on the Blade Element Theory (BET), which is a well known method applied to design and performance analysis of wind and hydrokinetic turbines, which usually present good agreement with experimental data. The results are compared with data obtained from hydrokinetic turbines designed by the classical Glauert's optimization. The present method yields good behavior, and can be used as an alternative tool in efficient hydrokinetic turbine designs.